Prevalence of mycoplasma-like lung lesions in pigs from commercial farms from Spain and Portugal - FJ Pallarés; JA Añón; IM Rodríguez-Gómez; J Gómez-Laguna; R Fabré; JM Sánchez-Carvajal; I Ruedas-Torres; L Carrasco (Porcine Health Management, 2021)
Abstract Background Mycoplasma hyopneumoniae causes a chronic respiratory disease that produces important economic losses due to poor productive performance, increased mortality and costs for several control strategies. The prevalence of mycoplasma-like lesions (MLL) at abattoir has been widely studied in different countries, making use of different scoring systems. However, most of them are difficult to apply in abattoirs with high number of pigs sacrificed per hour. For that reason, it is necessary to adapt the scoring system to the reality of the modern abattoir, even if there is a loss of accuracy. Our purpose was to investigate the prevalence and severity of MLL at abattoirs in Spain and Portugal using a 0 to 5 scoring system adapted to abattoirs with high number of sacrificed pigs per hour and to highlight the histopathological diagnosis as confirmatory method to identify patterns of pneumonia correlated to gross lesions. Results Cranioventral pulmonary consolidation, a typical MLL, was the most frequent lung lesion (30.97 %) detected at the abattoir, followed by dorsocaudal infarcts with pleurisy (12.51 %) and pleurisy alone (6.26 %). The average score for all examined lungs at abattoir was 1.99 out of 5 points. The histopathological study revealed that the 78.17 % of the randomly selected lungs with MLL presented microscopic lesions compatible with M. hyopneumoniae infection. Most bronchointerstitial and interstitial pneumonia lesions had a chronic course while most suppurative and fibrinous bronchopneumonia lesions had an acute course and a higher degree of severity. The combination of microscopic lesions more frequently observed was bronchointerstitial pneumonia + interstitial pneumonia + suppurative bronchopneumonia. Conclusions The prevalence of MLL at abattoir was 30.97 %, however, after microscopic examination the real prevalence of lungs with lesions compatible with M. hyopneumoniae infection was reduced up to 24.21 %. The six more prevalent combinations of lesions in the microscopic study involved the 66.13 % of examined lungs, and in all of them, microscopic lesions characteristic of M. hyopneumoniae infection were found, what supports the importance of M. hyopneumoniae as a primary pathogen in cases of PRDC.